Sport Events for Sport Participation: A Scoping Review - Teare, Georgia; Taks, Marijke (Frontiers in Sports and Active Living, 2021)
Research on sport participation impacts from sport events has been sporadic. This scoping review assesses the current state of literature that addresses impacts, legacies, and leveraging of sport events for sport participation outcomes, and the gaps in terms of study context and research designs. Two systematic approaches of article identification were performed: a traditional database search and a systematic manual search. Studies on sport participation outcomes from events mainly focused on mega sport events, adult populations, with the majority employing cross sectional data and quantitative methods. The use theoretical of frameworks is limited and inconsistent. There is a need for longitudinal investigations, as well as more focus on youth populations, participant events, and smaller sized events to advance the research agenda for sport participation outcomes from sport events.